Investigation on different vertical aerated rock filter (vertical aerated rock filter) in removing phosphorus from domestic wastewater - Maarup, Syahrul Nizam (2021)
Nutrients in the water body encourage the growth of algae which can accelerate eutrophication. Rock filter (RF) has appeared as an alternative technology to remove phosphorus from wastewater. In response to this, the selection of media between steel slag and limestone for pilot scale filter has been investigated by receiving the same volumetric hydraulic loading rate and airflow rate. Based on the analysis, steel slag emerged as the best media in removing the selected parameters. Therefore, the vertical aerated steel slag filter (VASSF) has been optimized with different hydraulic loading rates (HLR) ranging from 0.16 to 5.44 m3/m3day and airflow rate ranging from 3L/min to 10L/min to enhance the removal of phosphorus. Based on the optimization study, total phosphorus (TP) removal was perfectly removed by using an airflow rate of 7L/min and HLR of 1.04 m3/m3.day. The VASSF was efficiently removed by 89%, 75%, 73%, 30% and 96% of biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), TP and total coliform respectively. Meanwhile, for the pH, the effluent value decreased by 56%, pH also rose to 7.3 and dissolved oxygen (DO) concentration increased up to 5.09 mg/L. Result from steel slag lab-scale study shows that for selected parameter was removed by about 99%, 94%, 97%, 58% and 96% meanwhile for limestone lab-scale study removed by about 95%, 94%, 98%, 64% and 100% of BOD, COD, TSS, TP and total coliform respectively. The mechanism for phosphorus removal study by using scanning electron microscopy (SEM/EDX) equipment has been conducted after a period of two months for testing. For the fresh steel slag sample, there is no phosphorus on the surface but for the treated steel slag sample, there are available on the surface. Based on phosphorus attachment on media it indicates that the adsorptions occur on the media and all parameters are in the permissible limit of standard B based on Malaysian Environmental Quality (Sewage) Regulation 2009.